2000
DOI: 10.1046/j.1471-4159.2000.0750282.x
|View full text |Cite
|
Sign up to set email alerts
|

The Postsynaptic Density Protein PSD‐95 Differentially Regulates Insulin‐ and Src‐Mediated Current Modulation of Mouse NMDA Receptors Expressed in Xenopus Oocytes

Abstract: Abstract:The NMDA subtype of glutamate receptor is physically associated with the postsynaptic density protein PSD-95 at glutamatergic synapses. The channel activity of NMDA receptors is regulated by different signaling molecules, including protein tyrosine kinases. Because previous results have suggested a role for protein kinase C (PKC) in insulin potentiation of NMDA currents in oocytes, the effects of coexpression of PSD-95 on insulin and PKC potentiation of NMDA currents from these receptors were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 28 publications
3
33
0
Order By: Relevance
“…These findings demonstrate that kinase-dependent phosphorylation regulates interaction of synaptic scaffolding proteins with NMDARs. Conversely, PSD-95 attenuates PKC potentiation of NMDARs expressed as the ratio of potentiated to control responses (26)(27)(28). However, the molecular mechanisms by which synaptic scaffolding proteins modulate kinase effects on NMDAR gating and trafficking are not well delineated.…”
mentioning
confidence: 99%
“…These findings demonstrate that kinase-dependent phosphorylation regulates interaction of synaptic scaffolding proteins with NMDARs. Conversely, PSD-95 attenuates PKC potentiation of NMDARs expressed as the ratio of potentiated to control responses (26)(27)(28). However, the molecular mechanisms by which synaptic scaffolding proteins modulate kinase effects on NMDAR gating and trafficking are not well delineated.…”
mentioning
confidence: 99%
“…One of the very important scaffolding proteins known to interact with NMDAR is PSD-95 (Kornau et al 1995;Niethammer et al 1996;Liao et al 2000;Roy et al 2002;Rutter et al 2002;Lavezzari et al 2003). Recently, it has been reported that PSD-95 interacts with GlyT1 and impairs its internalization (Cubelos et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings suggest that the 95 kDa postsynpatic density protein, PSD-95, acts as a scaffolding for associating NMDA receptors and protein kinases (Tezuka et al 1999), and PSD-95 appears to play a role in controlling kinase modulation of NMDA receptor currents (Liao et al 2000). Further, A-kinase anchoring proteins (AKAPs) such as AKAP79/150 provide a scaffold for signaling enzymes, PKA and PKC (Klauck et al 1996).…”
Section: Introductionmentioning
confidence: 99%